Synthesis, Structure, Magnetic and Photoluminescent Properties of Dysprosium(III) Schiff Base Single‐Molecule Magnets: Investigation of the Relaxation of the Magnetization. Issue 17 (28th July 2020) - Long, Jérôme; Basalov, Ivan V.; Lyssenko, Konstantin A.; Cherkasov, Anton V.; Mamontova, Ekaterina; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract: We report here the synthesis, structure, magnetic and photoluminescent properties of three new bifunctional Schiff‐base complexes [Dy(L1 )2 (py)2 ][B(Ph)4 ]⋅py (1 ), [Dy(L1 )2 Cl(DME)] ⋅ 0.5DME (2 ) and [Dy(L2 )2 Cl] ⋅ 2.5(C7 H8 ) (3 ) (HL1 =Phenol, 2, 4‐bis(1, 1‐dimethylethyl)‐6‐[[(2‐methoxy‐5‐methylphenyl)imino]methyl]; HL2 =Phenol, 2, 4‐bis(1, 1‐dimethylethyl)‐6‐[[(2‐methoxyphenyl)imino]methyl]). The coordination environment of the Dy 3+ ion and the direction of the anisotropic axis may be controlled by the combination of the substituent groups of the Schiff bases, the nature of the counter‐ions (Cl − vs . BPh4 − ) and the coordinative solvent molecules. A zero‐field slow relaxation of the magnetization is evidenced for all complexes but strong differences in the relaxation dynamics are observed depending on the Dy 3+ site geometry. In this sense, complex 1 exhibits an anisotropy barrier of 472 cm −1, which may be favourably compared to other related examples due to the shortening of the Dy−O bond in the axial direction. Besides, the three complexes exhibit a ligand‐based luminescence making them as bifunctional magneto‐luminescent systems. Abstract : The synthesis, structures, magnetic and photoluminescent properties of three dysprosium Schiff‐base complexes acting as single‐molecule magnets are reported. The coordination environment of the Dy 3+ ion may be controlled by the combination of the substituent groups, the counter‐ions and the coordinative solvent molecules. The shortening of the Dy−O(phenoxide) distance induces an enhancement of the anisotropy barrier.